Asymmetric traffic provisioning in integrated cloud-fog based on flexible multi-flow optical transponder - Kim, Geun Soo; Kim, Jae Hoon; Peng, Limei (China Communications, 2019)
To accommodate the asymmetric characteristic of Internet traffic, we propose a flexible node architecture based on multi-flow optical transponders (MF-OTP) under the integrated Cloud-Fog framework. The proposed MF-OTP architecture is flexible in the following two degrees. Firstly, it can be flexibly adjusted to transmit either downstream or upstream traffic according to the timely traffic demand distribution. Secondly, it allows multiple sub-channels using flexible (i.e., same/different) modulation formats to serve the same traffic demand. To evaluate the efficiency of the flexible MT-OTP in serving asymmetric traffic, we propose two integer linear programming (ILP) models to address the routing, modulation and spectrum assignment (RMSA), with one aiming at minimizing the required number of sub-channels and another aiming at maximizing the volume of traffic transmission. Numerical simulations are conducted and the results show that the proposed models based on the flexible MF-OTP architecture requires less number of sub-channels and can serve more traffic demands.
Keywords: flexible MF-OTP; fog computing; ILP; traffic asymmetric